Integrasi Perubahan Temporal dalam Bisnis Digital: Pendekatan Teori Proses dan Pemodelan Berbasis Agen dalam Era Transformasi Digital - Rasyad, Rizky Zakariyya; Mawardah, Putri Nuraini (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The study aims to analyze temporal change in digital business through the integration of process theory and agent-based modeling. The approach is used to understand how technology adoption evolves over time through the interaction of user perception, network influence, and organizational response. The research method consists of two stages, namely process mapping and simulation of technology adoption involving 200 agents classified as innovators, early majority, and late majority. Key variables include perceived ease of use, perceived usefulness, network influence, and system usage level. Simulation results show an increase in adopters from 20 agents at T0 to 180 agents at T3, accompanied by a rise in average perceived ease of use from 3.5 to 4.5 and perceived usefulness from 3.6 to 4.6. Network effects accelerate adoption, especially after innovators establish usage legitimacy for other groups. Findings indicate that digital transformation progresses gradually and is shaped by the interaction among actors, technology, and organizational readiness. The integration of process theory and agent-based modeling supports adaptive strategy, strengthens organizational resilience, improves digital business performance, enables more effective decision-making, and sustains adoption processes within rapidly changing digital environments.